VÍTIMA DE TRÂNSITO COM MOTO, POLITRAUMATISMO E RUPTURA DE VÍSCERAS: UM ESTUDO DE CASO - Mayer, Bárbara L. D.; Wildner, Laura E. S.; Herr, Gerli E. G.; Rosanelli, Cleci L. S. P. (Salão do Conhecimento, 2013)
Resumo